Inside Cover: A Pan Photoaffinity Probe for Detecting Active Forms of Matrix Metalloproteinases (ChemBioChem 1/2013). Issue 1 (23rd December 2012) - Nury, Catherine; Czarny, Bertrand; Cassar‐Lajeunesse, Evelyne; Georgiadis, Dimitris; Bregant, Sarah; Dive, Vincent
<x xml:space="preserve">Abstract</x> The inside cover picture shows the simultaneous labelling under photoirradiation of four MMP catalytic domains with a photoactivable phosphinic MMP inhibitor inside 40 mg of proteome. The specific and sensitive detection of MMP covalent complexes was achieved by radioimaging. For further details see the paper by V. Dive et al. on p. 107 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>